Effect of foaming agents on drying characteristics and physicochemical properties of foam mat dried jackfruit powder - Chew, Ying (2021)
Although jackfruit (Artocarpus heterophyllus) is highly nutritious fruit yet it is easily perishable and has limited shelf life in nature. In spite of vast potential and usefulness, jackfruit remain as an underutilized fruit. A gap in the marketing of jackfruits and its processed value-added products can be fully explored in order to gain additional attention from food technology and security. The aims of this study are to determine the effect of different types and concentration of foaming agents on drying characteristics of foam mat drying jackfruit and to evaluate the effect of foam mat drying process variables on the physicochemical properties of foam mat dried jackfruit powder using various foaming agents, namely maltodextrin (5 to 20 %), methylcellulose (5 to 20 %) and gum arabic (0.5 to 2.0 %) at constant temperature (50°C) and thickness (3 mm) were conducted. The results showed that the drying characteristic of foam mat dried jackfruit was best fitted to the Page model as high correlation R2 > 0.88 was obtained. The results showed foaming agents were significantly factor that affect the physical properties, phytochemical content and antioxidant. In general, increased concentration of foaming agents reduced the foam density, moisture content, water activity, water absorption index, but increased color, water solubility index, flowability and bioactive compound. Rapid drying rate was observed when high foam expansion and low foam density was achieved subsequently resulting in reduction of drying time by increasing concentration of foaming agents. Shorter the drying time, higher the retention of bioactive properties in jackfruit powder. The optimum powder was formulated with 15% of gum arabic was recommended to provide superior flowability characteristic and excellent retention of phenolic, flavonoid and carotenoid in production of foam mat dried jackfruit powder. This contribution can be applied in future food product development such as ice cream, functional food and confectionery products.